The Role of Bawaslu Palangka Raya City in Maintaining the Neutrality of the State Civil Apparatus in 2024 General Election - Pahrina; Suriansyah Murhaini; Ivans Januardy (Journal of Law, Politic and Humanities, 2025)
General Elections (Pemilu) are a means of implementing the sovereignty of the people as stipulated in the 1945 Constitution of the Republic of Indonesia, which is carried out directly, publicly, freely, confidentially, honestly, and fairly. One of the main challenges in organizing elections is maintaining the neutrality of the State Civil Apparatus (ASN), which is legally prohibited from engaging in practical politics. The neutrality of ASN is a serious concern because their non-neutrality can affect the integrity of the election process and reduce public confidence in the results obtained. In the context of the 2024 Election, the role of the General Election Supervisory Agency (Bawaslu) of Palangka Raya City is very important in ensuring the neutrality of ASN. This study aims to analyze the role of the Election Supervisory Agency (Bawaslu) of Palangka Raya City in maintaining ASN neutrality during the 2024 Election and to examine the supervision strategy implemented to handle violations of ASN neutrality. Through systematic monitoring, strict law enforcement, and socialization of the importance of ASN neutrality, it is hoped that Bawaslu can ensure the holding of fair and democratic elections.